A leitura dos contos de fadas na perspectiva do interacionismo sociodiscursivo - Dias, Suzete Silene Soares (2018)
This research promotes a case study that investigates possibilities of developing a reading proposal with fairy tales that promotes reflections on the values linked to traditional societies and contemporary societies inscribed in the texts read. It examines the different forms of representation of women in the fairy-tale genre, pointing to different ways of acting and thinking in fictionally constructed worlds from Coelho (2012). Such activities of analysis were carried out with students of a 7th grade elementary school class of a public school in Bahia, seeking to prove possibilities of developing reading activities with questions about the social values enrolled in literary works. Taking as a starting point the historical study of children's literature, it is observed that literary texts always point to different worldviews that are articulated to the context of the production of their writing and the moment in which the interaction with the readers is realized . The main reading strategy is to understand the context of production of fairy tales and the intertextual process in order to identify conservative values and emancipatory values of women. To exemplify this process, four fairy tales were produced, one produced in the seventeenth century, the other in the nineteenth century and two in the twentieth century. The values are analyzed through the observation of the behavior of the female characters and the outcome that narrative presents. The procedures adopted by Sociodiscursivo Interacionismo (hereinafter ISD) are used as an analysis contribution. Bronckart's notion of architects (2006), the notions of production conditions and the textual infrastructure (general plan, types of discourses, and sequence types) in Bronckart (1999) and the understanding of didactic sequence (SD) developed by Dolz ; Noverraz and Schneuwly (2011). At the end, there is a didactic sequence that contains the following steps: presentation of the initial situation, initial production - the proposition of an activity of interpretation of the traditional tales "Rumpelstiltskin" of Brother Grimm, Perrault's Donkey Skin, in contrast to two contemporary tales by Marina Colasanti The Weaver Girl and Between the Sword and the Rose, Twelve Modules, Intermediate Production and Final Production.